High Prevalence and Predictors of Maternal Anemia Risk: Nationwide Midwife-Reported Screening in Indonesia - Ade Jubaedah; Herlyssa Herlyssa; Hetty Astri; Innana Mardhatilla; Fitriani Fitriani; Ery Suhaerlinah; Ray Wagiu Basrowi; Dessy Pratiwi; Nova Lidia Sitorus (Healthcare, 2026)
Background: Maternal anemia remains a major public health concern in low- and middle-income countries, including Indonesia, where access to hemoglobin and iron-status measurements remains uneven. Although non-laboratory screening cannot confirm anemia or iron deficiency, digital collection of anemia-related symptoms, clinical signs, nutritional indicators, and reproductive risk factors may support preliminary risk identification in settings with limited diagnostic capacity. This study aimed to describe the nationwide implementation of a digital composite anemia-risk checklist and to examine maternal, reproductive, and regional factors associated with screening-positive status among pregnant women in Indonesia. Methods: A retrospective cross-sectional study was conducted using secondary data recorded through the e-Nutri mobile application during routine antenatal care from February to April 2025. The analysis included 205,822 pregnant women recorded across all 34 Indonesian provinces. Screening-positive anemia-related risk was defined operationally as at least one positive response among ten checklist indicators. Associations between maternal age, gestational age, parity, birth spacing, geographic region, and screening-positive status were examined using Poisson regression with robust variance estimation to obtain adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs). Results: Overall, 65.3% of participants met the operational criterion for screening-positive anemia-related risk. Multiparity was associated with a higher prevalence of screening-positive status (aPR 1.20; 95% CI 1.19–1.21), as was a birth interval of less than two years (aPR 1.10; 95% CI 1.09–1.11). Screening-positive status was slightly less prevalent during the second and third trimesters than during the first trimester. Compared with Sulawesi, the adjusted prevalence was higher in Kalimantan and lower in Sumatra and Maluku–Papua. Although 91.6% of participants reported iron supplementation use, the available data did not measure dosage, duration, adherence, or biochemical response. Conclusions: Nearly 7 of 10 pregnant women are at risk of anemia. Digital symptom-based screening conducted at a national scale identified widespread maternal anemia risk and consistent associations with cumulative reproductive burden and regional context. This approach potentially offers an alternative complement to laboratory-based surveillance in resource-limited settings.